Methods of speed-strength training for young freestyle wrestlers - N.M. Sanсharova; G.O. Ogar; Ye.O. Gunko (H.S. Skovoroda Kharkiv National Pedagogical University, 2018)
The goal is to develop a method of speed-strength training for young freestyle wrestlers and to prove its effectiveness experimentally. Research participant. In research young wrestlers - the first sports category which sports experience made 4-5 years took part, age of athletes was 14 (n=10) - 15 (n=10) years. All of them were engaged in groups of sports improvement. Research methods: analysis of scientific and methodological sources, pedagogical observations, pedagogical testing, mathematical statistics. Results. The results of the study prove that the technique used in the experimental group, which included an increase in the means of speed-strength training, was more effective than the training program of the control group. This is due to the use of a wide range of General and special means of speed-power orientation and methods aimed at the education of speed-power abilities of athletes proposed in the experimental technique. Thus, the experimental group under study significantly improved the General and special speed-strength readiness during the execution of the experimental training program. Summary. The developed experimental technique showed that the increase in the volume of speed-strength exercises in the training process should be considered as one of the ways to improve the efficiency of the system of sports training of young wrestlers. It was established that application in educational and training process of young wrestlers of 14-15 years, a technique with the accented speed and power orientation, within 8 weeks, allows to increase significantly level of their General and special speed and power readiness. The proposed method should be used in the training process of athletes whose qualifications are not lower than the first sports category, and the experience of training-at least four years.